2022
DOI: 10.21037/jovs-21-5
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic management of patients with excessive central airway collapse: a narrative review

Abstract: To provide a narrative review of the novel endoscopic approaches available in the literature for the treatment of excessive central airway collapse (ECAC). ECAC is characterized by excessive expiratory collapse of the central airway which can lead to dyspnea, cough, difficulty clearing secretions and recurrent respiratory infections. Surgical stabilization of the airway via tracheobronchoplasty (TBP) has been considered the standard of care for patients who have severe symptomatic ECAC despite optimal medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…( 2 , 9 ). In select patients who are not surgical candidates, CPAP may be a feasible alternative for long‐term management or adjunctive to TBP for those with residual symptoms ( 10 ). Nonetheless, the long‐term efficacy of NIPPV has not been unequivocally established ( 2 , 7 , 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 2 , 9 ). In select patients who are not surgical candidates, CPAP may be a feasible alternative for long‐term management or adjunctive to TBP for those with residual symptoms ( 10 ). Nonetheless, the long‐term efficacy of NIPPV has not been unequivocally established ( 2 , 7 , 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…In select patients who are not surgical candidates, CPAP may be a feasible alternative for long‐term management or adjunctive to TBP for those with residual symptoms ( 10 ). Nonetheless, the long‐term efficacy of NIPPV has not been unequivocally established ( 2 , 7 , 9 , 10 ). The mechanism behind NIPPV is pneumatic stenting, which is defined by increased transmural pressure in the central airway due to increased intraluminal pressure on the trachea from NIPPV, expanding the cross‐sectional area of the airway lumen ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…8 The benefit of USEMAS over silicone stents in this context is attributed to their capacity to preserve the airway's innate mucociliary clearance and superior inner diameter-to-wall thickness ratio. 25 This improved functionality allows the stent evaluation to serve as a better predictor of response to TBP. By reducing complications, USEMAS can ensure that the benefits of airway stabilization are not confounded, making them a valuable choice for stent evaluations in ECAC.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, short-term stenting is the preferred predictor for potential improvement after TBP due to its immediate central airway stabilization [ 9 ]. Significant objective improvement following stent trial has been reported in 65–75% of patients [ 10 , 11 ]. However, some patients may be unsuitable for this invasive trial and present related complications such as granulation tissue formation, intractable cough, valve migration, mucus plugs, or impaction, that could lead to the narrowing of the lumen or worsening symptoms, especially in cough phenotypes.…”
Section: Discussionmentioning
confidence: 99%